Marketing Strategy Of Raw Barabir Crackers Production UD. Barokah, Mangli District, Jember Regency: Strategi Pemasaran Kerupuk Barabir Mentah Produksi UD. Barokah Kecamatan Mangli Kabupaten Jember - Universitasari, Pascawati Savitri; Permatasari, Sylvia Leoni; Iskandar, Ridwan; Ambarkahi, Ratih Puspitorini Yekti; Wiguna, Ardhitya Alam; Nugraheni, Ponti Primastuti Aulia; Mayasari, Financia (Indonesian Journal Publisher, 2024)
The research location is at UD. Barokah, Mangli District, Jember Regency. This business was founded in 1999. This study aims to 1) Identify the strengths, weaknesses, opportunities and threats in the Barokah Barokah UD Barokah cracker business, Mangli District, Jember Regency, 2) To formulate an alternative marketing strategy in the UD Barokah Barokah cracker business, Mangli District, Jember Regency, 3) To determine the priority of the marketing strategy in the Barokah UD Barokah cracker business, Mangli District, Jember Regency. The analysis technique used is SWOT analysis and QSPM analysis. The results of the SWOT analysis show that the company's position is in cell II where the right strategy is a growth and development strategy. Based on the results of the calculation of the QSPM analysis which is the main strategy priority at UD. Barokah is expanding market share by making the latest product innovations with a TAS score of 7.67.